Absence of specific mucosal antibody responses in HIV-exposed uninfected sex workers from the Gambia. - Dorrell, L; Hessell, A; Wang, M; Whittle, H; Sabally, S; Rowland-Jones, S; Burton, DR; Parren, P (2000)
OBJECTIVES: Specific antibodies to HIV envelope that inactivate virus at the mucosal surfaces involved in sexual contact are of interest for the design of a vaccine against HIV-1. It has been suggested that, in frequently HIV-exposed but uninfected individuals, HIV-specific mucosal antibody responses may exist and play a role in resistance against HIV. This study investigated HIV-1 envelope specific mucosal antibody responses in HIV-resistant sex workers in west Africa. METHODS: A group of 26 exposed uninfected female commercial sex workers from the Gambia, who have had repeated exposures to HIV-1 and HIV-2 were studied. We assessed the presence of vaginal IgA and IgG in vaginal swabs against a range of HIV-1 and HIV-2 envelope presentations and performed HIV-1 neutralization assays. RESULTS: No significant vaginal IgA or IgG responses against HIV-1 or HIV-2 were detected, and none of the vaginal secretions tested displayed any HIV-1 neutralizing activity. CONCLUSION: Vaginal antibody responses against HIV were not found in Gambian sex workers who resist HIV infection. Resistance against HIV infection can therefore occur in the absence of specific antibodies against HIV at the genital mucosa. A protective role for HIV-envelope specific IgA in resistance against HIV-1 infection in exposed uninfected individuals as reported in the literature is uncertain.